PARTICIPATION IN STUDENT SELF-GOVERNMENT BODIES AS A FACTOR IN THE DEVELOPMENT OF LEADERSHIP QUALITIES OF STUDENT YOUTH - Хоменко-Семенова, Леся; Шевченко, Ігор; Оксамитна, Леся (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article provides a theoretical analysis and empirical research into the problem of developing leadership qualities of student youth in student self-government bodies. The purpose of the article is to prove the influence of participation in student self-government bodies on the development of students’ leadership qualities; Results. In the course of the empirical study, we used the following methods: Methodology "I am a leader" (E.S. Fedorov, O.V. Eryomin, modified by T.A. Mironova); Methodology "Diagnostics of leadership abilities" (E. Zharikov, E. Krushelnytsky; Methodology for diagnosing communicative and organizational inclinations - KOS (V. Sinyavsky and B. Fedoryshyn); Methodology "Self-assessment of leadership" (O.M. Kokun). The results of the study were processed using the following methods of mathematical statistics: to determine the relationship between leadership abilities and gender, the Pearson criterion; to assess the reliability of differences between groups, the t-Student criterion was used; Statistical calculations were performed using the Microsoft Excel XP computer program package. Conclusion. After conducting the study, we established that the leadership qualities of students are a set of personal qualities, such as: activity, motivation, desire for self-improvement, empathy and the ability to influence others, which allow student leaders to effectively achieve goals, serving by example and motivating peers. In higher education institutions, student self-government is an important mechanism for developing students’ leadership potential. It creates an environment for the formation of responsibility, communication skills, organizational skills and social activity. The training "The Art of Leadership" was developed, the purpose of which is to develop the leadership qualities of student youth through their participation in student self-government bodies. After the training, a re-sampling showed positive dynamics in all indicators. A correlation analysis was carried out using the Pearson correlation coefficient, which showed that the development of one of the skills or inclinations contributes to the improvement of other important aspects of personal and professional development, which is valuable in the formation of leadership qualities and effective interpersonal interaction. Key words: leader; leadership; leadership qualities; student youth; emotional intelligence; self-esteem; motivation.